Modified Cellulose Membranes Show High Performance for Oil–Water Separation in Wastewater Treatment - Ian Kurniawan (Science Journal Get Press, 2026)
Efficient separation of oil–water emulsions is critical for environmental protection and industrial wastewater treatment. In this study, cellulose membranes were surface-modified by introducing hydrophilic functional groups to enhance hydrophilicity, permeability, and antifouling performance. The modified membrane exhibited a significant decrease in water contact angle from 46.3° to 12.8°, indicating markedly improved wettability. FTIR and XRD analyses confirmed successful surface modification without altering the crystalline structure of cellulose. Compared to the pristine membrane, the modified membrane showed increased porosity (78.6%) and water uptake (126.4%), leading to enhanced pure water flux (3,420 L·m⁻²·h⁻¹) and stable oil–water emulsion flux (2,680 L·m⁻²·h⁻¹), with an oil rejection efficiency exceeding 99%. The membrane also demonstrated superior antifouling performance, with a flux recovery ratio of 91.3%, and maintained high separation efficiency over multiple filtration cycles, indicating excellent reusability and operational stability. These results demonstrate that surface modification is an effective strategy for developing high-performance and sustainable cellulose membranes for oil–water separation in wastewater treatment applications.